Constitutional law of India - Pandey, J.N.; Tripathi, H.C.P. (fwd.) (Prayagraj: Central law agency, 2023)
Dr. J. N. Pandey's Constitutional Law is considered as an authoritative work that provides, in a lucid yet vivid fashion, a meticulous discussion of the fundamental concepts of the sacrosanct Constitution.
Keywords: Constitutional law; India